In silico screening and molecular dynamics simulations toward new human papillomavirus 16 type inhibitors - Nima Razzaghi-Asl; Sahar Mirzayi; Karim Mahnam; Vahed Adhami; Saghi Sepehri (Wolters Kluwer Medknow Publications, 2022)
Background and purpose: Human papillomavirus (HPV) is known as the main reason for cervical cancer. According to carcinogenic risk, HPV can be located into two classes, counting the low-risk virus, which is the main cause of genital warts and low-grade cervical epithelial lesions. HPV-16 is one of the high-risk HPV subtypes in the spectrum of cervical diseases. Experimental approach: The PubChem database was screened in order to identify potential anti-HPV hits followed by ADMET predictions. Then, molecular docking was performed to improve the accuracy of screening and also to find the details of the interactions of the hit compounds with the active site. Finally, molecular dynamic (MD) simulations and free binding energy on top-ranked structures CID_73212812, CID_91059286, CID_69838075, cidofovir, and jaceosidin were carried out with protein to compute the interaction energies and stability of the top-ranked compounds at the active site. Findings/Results: Based on molecular docking studies, three compounds including CID_73212812, CID_91059286, and CID_69838075 exhibited the best results among compounds against the E6 protein of HPV-16. Furthermore, RMSD, RMSF, hydrogen binds, Rg, and energy analysis during MD simulation certainly indicated the stable binding of selected compounds with E6 protein of HPV-16 active site. Conclusion and implications: Docking and MD results revealed that hydrophobic contacts and optimum hydrogen bonds were determinant factors in the interactions of hits and the E6 protein of HPV-16. In addition, the binding energy portions exposed that Van der Waals and non-polar interactions were fundamental factors in the molecule binding.